(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, the role of fine art in the development of human artistic culture and spirituality, the artist’s work depicting events and objects that are not only a product of human fantasy, but also events that exist in life are some of the phenomena that exist in life. changing and exaggerating aspects are explained.